Exploring the association between loneliness, work environment, and depressive symptoms: evidence from young Korean workers in the Seoul Metropolitan Area - Geon Lee; Chulwoo Kim (Frontiers in Public Health)
BackgroundMental health in the workplace is an emerging public health concern, particularly for young workers who may experience challenges that contribute to psychological distress. This study examined the associations between loneliness, work environment, and depressive symptoms among young workers in Seoul, South Korea.MethodsA cross-sectional survey was conducted among young workers in Seoul to assess workplace conditions, job satisfaction, workplace bullying, and depressive symptoms. Negative binomial regression analysis was used to evaluate the associations between selected workplace factors, including job-major alignment, commute time, workplace bullying, job satisfaction, and mental health outcomes.ResultsA negative association was found between job satisfaction and depressive symptoms, and a positive association was found between workplace bullying and depressive symptoms. Job–major alignment and commute time were not significantly related to depressive symptoms. The findings also highlighted a meaningful relationship between workplace social connections and loneliness among young workers.ConclusionThese results suggest that workplace conditions, such as job satisfaction and social climate, may be important factors in understanding depressive symptoms among younger working populations. Given that the data were limited to young workers in Seoul, future research should adopt a longitudinal design and conduct comparative studies across different regions and countries to gain a more comprehensive understanding of workplace mental health.